The Impact of Lifestyle on Zakat Payment: A Behavioral Study of Muslim Communities - Krisnanda Krisnanda (Yayasan Nurul Musthafa, 2025)
Lifestyle reflects a community's identity, encompassing patterns of behavior, daily activities, interests, and financial priorities. It shapes how individuals allocate their time and resources, influencing their social and religious practices. This study examines the relationship between lifestyle and zakat payment within Muslim communities. Using the Weighted Least Squares (WLS) method for data analysis, this research investigates how lifestyle factors influence individuals’ decisions to fulfill zakat obligations. The study employs a non-probability sampling approach with an accidental sampling technique, selecting respondents based on their relevance to the research. The findings reveal a significant correlation between lifestyle and zakat payment, indicating that an individual's lifestyle plays a crucial role in their commitment to religious giving. These results provide valuable insights into the behavioral aspects of zakat payment, highlighting the broader implications of lifestyle in shaping religious and charitable practices, as demonstrated by the t-value in the partial test (t-test). [Gaya hidup mencerminkan identitas suatu komunitas, mencakup pola perilaku, aktivitas sehari-hari, minat, dan prioritas keuangan. Gaya hidup membentuk cara individu mengalokasikan waktu dan sumber daya mereka, serta memengaruhi praktik sosial dan keagamaan. Penelitian ini mengkaji hubungan antara gaya hidup dan pembayaran zakat dalam komunitas Muslim. Dengan menggunakan metode Weighted Least Squares (WLS) untuk analisis data, penelitian ini mengeksplorasi bagaimana faktor gaya hidup memengaruhi keputusan individu dalam memenuhi kewajiban zakat. Studi ini menerapkan pendekatan non-probability sampling dengan teknik accidental sampling, di mana responden dipilih berdasarkan relevansi mereka terhadap penelitian. Hasil penelitian menunjukkan adanya korelasi yang signifikan antara gaya hidup dan pembayaran zakat, yang mengindikasikan bahwa gaya hidup individu memiliki peran penting dalam komitmen mereka terhadap pemberian zakat. Temuan ini memberikan wawasan berharga tentang aspek perilaku dalam pembayaran zakat, serta menyoroti dampak luas gaya hidup dalam membentuk praktik keagamaan dan amal, sebagaimana ditunjukkan oleh nilai t dalam uji parsial (t-test).]